(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
A new, simple, precise, accurate, and reproducible RP-HPLC for stability-indicating method development and validation of Ledipasvir and Sofosbuvir in bulk form. Separation ofLedipasvir and Sofosbuvir was successfully achieved Dona Zorbax C8, 250 X4.6mm, 5µm or equivalent in an isocratic mode utilizing 0.1% OPA: Methanol (45:55) at a flow rate of 1.0mL/min and the eluate was monitored at 238nm, with a retention time of 3.303 and 7.303minutes for Ledipasvir and Sofosbuvir respectively. The method was validated and their response was found to be linear in the drug concentration range of 45µg/ml to135 µg/ml for Ledipasvirand 200µg/ml to 600 µg/ml for and Sofosbuvir. The values of the correlation coefficient were found to 0.999 for Ledipasvirand 1 for Sofosbuvir respectively. The LOQ for Ledipasvirwere found to be 0.695 respectively. The LOQ for Sofosbuvir was found to be 2.2063 respectively. This method was found to be a good percentage recovery for Ledipasvir and Sofosbuvirwere found to be 100 and 100 respectively indicates that the proposed method is highly accurate. The specificity of the method shows a good correlation between retention times of standard with the sample so, the method specifically determines the analyte in the sample without interference from the excipients of tablet dosage forms. The method was extensively validated according to ICH guidelines for Linearity, Accuracy, Precession, Specificity, and Robustness.